1994
DOI: 10.1002/pen.760341004
|View full text |Cite
|
Sign up to set email alerts
|

Nonisothermal elongational behavior of blends with liquid crystalline polymers

Abstract: a l e m 901 28 P a l e m , Italy Measurements of melt strength and breaking stretching ratio of several blends of thermoplastic polymers with liquid crystalline polymers are presented. The melt strength behavior depends not only on the viscosity of the blends but also on the temperature dependence of the viscosity. In particular, even if the viscosities of the blends are, at the extrusion temperature, lower than that of the thermoplastic matrices, the melt strength can be larger than that of the pure thermopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 26 publications
(7 reference statements)
1
0
0
Order By: Relevance
“…Most of the studies reported in the literature on the evaluation of the polymer rheological properties in elongational flow have been carried out in isothermal conditions, while less attention has been devoted to the rheological behavior of polymer melts experiencing non-isothermal elongational flow, notwithstanding its technological relevance for the assessment of the processing behavior of polymer melts. Similar to what was observed in the previous section, polyethylene-and polypropylene-based materials are the most investigated materials, given the widely exploitation of these polyolefins in processing operations, in which the non-isothermal elongational flow is prominent [78][79][80][81].…”
Section: Rheological Properties In Non-isothermal Elongational Flowsupporting
confidence: 61%
“…Most of the studies reported in the literature on the evaluation of the polymer rheological properties in elongational flow have been carried out in isothermal conditions, while less attention has been devoted to the rheological behavior of polymer melts experiencing non-isothermal elongational flow, notwithstanding its technological relevance for the assessment of the processing behavior of polymer melts. Similar to what was observed in the previous section, polyethylene-and polypropylene-based materials are the most investigated materials, given the widely exploitation of these polyolefins in processing operations, in which the non-isothermal elongational flow is prominent [78][79][80][81].…”
Section: Rheological Properties In Non-isothermal Elongational Flowsupporting
confidence: 61%